Imaging Modalities for Cervical Spondylotic Stenosis and Myelopathy. (20th July 2011) - Green, C.; Butler, J.; Eustace, S.; Poynton, A.; O'Byrne, J. M.
Abstract : Cervical spondylosis is a spectrum of pathology presenting as neck pain, radiculopathy, and myelopathy or all in combination. Diagnostic imaging is essential to diagnosis and preoperative planning. We discuss the modalities of imaging in common practice. We examine the use of imaging to differentiate among central, subarticular, and lateral stenosis and in the assessment of myelopathy.